(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Necrotizing enterocolitis (NEC) is among common cause of mortality and morbidity in neonates particularly in preterm babies. In preterm neonates, the NEC has been reduced with the use of various probiotics. This study examined the impact of routine use of a probiotics (Ecotec sachet 2.0g) in preterm neonates for developing NEC. Objective: To compare the frequency of necrotizing enterocolitis (NEC) in preterm newborns with and without probiotics treatment. Materials and Methods: This randomized controlled trial study was carried out on neonates admitted during 21-4-2014 to 21-10-2014 at Neonatal intensive care unit of Fatima Memorial Hospital Lahore. A total of 140 neonates meeting the inclusion criteria were selected. Cases were registered for the study and demographic information of the patients (name, gestational age, sex and address) was documented. Study population was divided into two equal groups. Group A received probiotics (Ecotec sachet 2.0g) once daily. Probiotics were started on starting of feeding mixed in milk of newborn and continued administration until hospital discharge. Group B received the placebo. Cases were assessed on daily basis regarding the clinical signs of NEC. Results: Total 140 preterm neonates were included in this study, 70 in probiotic group and 70 in control group. The frequency of NEC was significantly low in the preterm neonates who received probiotics (3 of 70 neonates [4.3%] versus 6 of 70 untreated preterm neonates [8.6%]). Conclusion: Prophylactic use of the probiotics result in prevention of necrotizing enterocolitis with statistically significant benefit. However, the optimum type of probiotic supplementation and their long-term effects need further study.